2007
DOI: 10.2320/matertrans.mk200704
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Phosphorus Micro-Segregation and Sulfide Precipitation in Rapidly Solidified Steel—Utilization of Impurity Elements in Scrap Steel

Abstract: Copper is one of the main residual elements in steel, especially in recycled scrap steel. Sulfur and phosphorus are two of the main impurities in steel, and it may result in a large emission of slag and CO 2 to remove them from steel. Utilization of these elements has been an important and difficult matter for metallurgist. In the present paper, the as-cast steels containing different concentrations of copper, sulfur and phosphorus are prepared by strip casting process or laboratory rapid solidification proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In a recent paper by present authors, 34) the interaction between the microsegragation of phosphorus and sulfide precipitation has been investigated in copper bearing low carbon steel. Phosphorus could retard the sulfide precipitation at high temperature, promotes more copper bearings and smaller sulfides precipitation at low temperature.…”
Section: Solute Element Rich Zone Around Sulfidementioning
confidence: 99%
“…In a recent paper by present authors, 34) the interaction between the microsegragation of phosphorus and sulfide precipitation has been investigated in copper bearing low carbon steel. Phosphorus could retard the sulfide precipitation at high temperature, promotes more copper bearings and smaller sulfides precipitation at low temperature.…”
Section: Solute Element Rich Zone Around Sulfidementioning
confidence: 99%
“…It has been widely reported that surface-active elements can affect the segregation of alloying elements. 9,25,[33][34][35][36][37] Regarding high-speed steels, Jiao et al 9) reported that Mg increases the segregation of C in the residual melt in M42 steel but decreases segregation of Mo. Yin et al 25) and Qu et al 36) found that RE decreases the segregation of C, Mo and V in the residual melt in M2.…”
Section: Formation Thermodynamics Of M 2 C and M 6 C Carbidesmentioning
confidence: 99%
“…Sulfur removal is well known to decrease the solidification range as well as changing the surface energies. [42][43][44] The properties of the liquid would then be totally different and could explain why the microsegregation intensity is lower for inoculated samples where the grain size is not affected. Further investigations need to be done to verify that hypothesis.…”
Section: Additional Precipitate Characterizationsmentioning
confidence: 99%